2022
DOI: 10.3390/healthcare10071331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ibuprofen Use on the Immune System Indicators and Force in Disabled Paralympic Powerlifters of Different Sport Levels

Abstract: Background: Paralympic powerlifting (PP) training is typically intense and causes fatigue and alterations in the immune system. Objective: To analyze whether IBU would affect performance and the immune system after training in PP. Methodology: 10 athletes at the national level (NL) and 10 at the regional level (RL) participated in the study, where force and blood indicators were evaluated after training. The study took place over three weeks: (1) familiarization and (2 and 3) comparison between recovery method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…We were able to identify three studies [ 89 , 90 , 91 ] covering the impact of specific pharmacological strategies on the immune system and inflammatory state in disabled athletes.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to identify three studies [ 89 , 90 , 91 ] covering the impact of specific pharmacological strategies on the immune system and inflammatory state in disabled athletes.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 42 , 43 , 44 , 45 , 46 ] explored the impact of post-exercise recovery in PP through physiological and biochemical assessments using different strategies. Aidar et al [ 42 ] conducted a randomized, placebo-controlled trial and recruited 10 PP athletes at the national level, aged 27.13 ± 5.57 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations